Influencia del empirismo en la gestión de servicios de Tecnologías de Información en la UNIVERSIDAD NACIONAL DE SAN MARTÍN-TARAPOTO - Ramírez Alva, Taína Licel (2014)
The following research "INFLUENCE OF EMPIRICISM IN THE MANAGEMENT OF INFORMATION TECHNOLOGY SERVICES AT THE NATIONAL UNIVERSITY OF SAN MARTIN", this research will demonstrate the overall objective, which is to show that empiricism influences the management of information technology services at the National University of San Martin, in the period from March to December 2013, to implement surveys to administrative employees of the National University of San Martín, this in order to measure users satisfaction. Likewise, information concerning processes, activities and management documents are there in the office computing and communications are collected, the same way about the rules of service management in public administration to have a livelihood and to perform the respective analysis was collected. As a result it was found that user satisfaction (administrative workers UNSM-T) is in the range of regularly representing 43.3 percent of respondents, also found computer equipment with 08 years old, 1238 of them are in bad condition or broken and management documents are there in the office computer and communications are scarce, compared with that should be in accordance with the rules of management of computer services in public administration.